COMPOSITIONAL TRADITION OF PALM-LEAF GEET GOVIND MANUSCRIPSTS IN ODISHA - Bhadauriya, Shiwani; Tyagi, Namita (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The history of art in the present day is any activity or man-made means of expressing thoughts, feelings, in a visual form, for aesthetics or communication purposes. From time to time the arts were classified into various forms. In the formation of culture from prehistoric times to the present, palm leaves have a special significance in the contribution of art, which is still a living art in Odisha. Palm leaf was extensively used for writing and illustration. Odisha is considered to be the richest state in terms of pothis. The role of Odisha State Museum in this is unique, which is making the visitors well acquainted with the palm leaf art of Odisha. A main feature is the writing work with illustrations on palm leaves. Even in the narrow gap of the palm leaf, artistic combination is formed on seeing it, in which sweet pothis have been created by establishing harmony in the art elements. Generally, picture composition means to organize various visual elements in an artistic way or to give them a beautiful arrangement. On the subject of combination, Indian and Western scholars have created many texts by explaining many theories, so on the basis of these principles, we will present a combinational interpretation of the palm leaf paintings of Gitagovind Pothi. In these palm leaf paintings, mainly elements like line, color, tone, shape etc. have been expressed and created. Like the elements of art, the principles of combination have their own importance, in the absence of which the combination cannot be successful. The 8 main principles of composition are repetition, harmony, opposition, proportion, balance, effectiveness, rhythm, and unity.